Linking primary care data from Clinical Practice Research Datalink to secondary care and other health-related patient data: update and implications - Chan, Justin; Barnett, Rhys; Hodgson, Susan; Chohan, Prinal; Mantovani, Giulia; Campbell, Jennifer (International Journal of Population Data Science, 2026)
Introduction Being able to accurately link primary and secondary healthcare records is invaluable for public health research. The Clinical Practice Research Datalink (CPRD) collects and curates primary care electronic health records from UK GP practices. These data are linked to secondary health data by National Health Service (NHS) England. As of 2020, NHS England introduced the Master Person Service (MPS) method to link data at the person-level. The method was first applied to CPRD data in the November 2024 linked data release. Objectives This paper provides an overview of the MPS linkage method and its impact on linked CPRD data. Methods The MPS linkage method searches each set of personal identifiers against records within the Personal Demographics Service and the MPS record bucket. Successful matches are assigned a patient identifier `Person_ID', which is used to link records between datasets. The number of successfully linked CPRD patients was compared between the MPS and the previous linkage method. The impact of the change in linkage eligibility definition was also examined. Results There are 7.9 million (CPRD GOLD) and 34.2 million (CPRD Aurum) patient records in the December 2024 primary care builds that are of research quality and were successfully linked to a Person_ID. Compared to the previous linkage method, the proportion of patient records who were defined as eligible to be linked to Hospital Episode Statistics Admitted Patient Care (HES APC) and had data in HES APC increased from 75.7% to 81.0% in CPRD GOLD and from 72.1% to 79.0% in CPRD Aurum. Conclusion The new linkage eligibility definition is superior to the previous definition, resulting in greater ability to define appropriate denominator populations and to differentiate why some patients do not have linked data. The MPS linkage method offers the potential for CPRD to investigate individuals with duplicate records and practice mergers.